2014
DOI: 10.1371/journal.pone.0112105
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Pseudomonas aeruginosa Phenotypic Plasticity by Quorum Sensing Dysregulation Hampers Pathogenicity in Murine Chronic Lung Infection

Abstract: In Pseudomonas aeruginosa quorum sensing (QS) activates the production of virulence factors, playing a critical role in pathogenesis. Multiple negative regulators modulate the timing and the extent of the QS response either in the pre-quorum or post-quorum phases of growth. This regulation likely increases P. aeruginosa phenotypic plasticity and population fitness, facilitating colonization of challenging environments such as higher organisms. Accordingly, in addition to the factors required for QS signals syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This could be necessary to modulate the QS response depending on specific environmental conditions, as previously suggested for other negative regulators of QS. For instance, the QteE and RsaL repressors in the human opportunistic pathogen Pseudomonas aeruginosa modulate the timing and extent of the QS response and likely increase P. aeruginosa phenotypic plasticity and population fitness, ultimately facilitating the colonization of challenging environments, including higher organisms (22,(28)(29)(30)(31)(32)(33). The RsaL protein is also found ubiquitously in the group of nonpathogenic plant-associated nitrogen-fixing Burkholderia spp., such as Burkholderia kururiensis, and its role is hypothesized to be a switch to turn on/off the AHL signaling system under various environmental conditions (22,34).…”
Section: Discussionmentioning
confidence: 99%
“…This could be necessary to modulate the QS response depending on specific environmental conditions, as previously suggested for other negative regulators of QS. For instance, the QteE and RsaL repressors in the human opportunistic pathogen Pseudomonas aeruginosa modulate the timing and extent of the QS response and likely increase P. aeruginosa phenotypic plasticity and population fitness, ultimately facilitating the colonization of challenging environments, including higher organisms (22,(28)(29)(30)(31)(32)(33). The RsaL protein is also found ubiquitously in the group of nonpathogenic plant-associated nitrogen-fixing Burkholderia spp., such as Burkholderia kururiensis, and its role is hypothesized to be a switch to turn on/off the AHL signaling system under various environmental conditions (22,34).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, rsaL mutation in P. aeruginosa PAO1 leads to enhanced surface motility and the production of secreted virulence factors such as elastase, hemolysins, hydrogen cyanide, and PYO. Conversely, when compared with the wild type strain, the rsaL mutation decreases the ability of this pathogen to cause chronic lung infections in mice (de Kievit et al, 1999;Rampioni et al, 2009;Bond ı et al, 2014). Notably, transcriptomic analyses revealed that RsaL has a negative impact on the expression of multiple genes, including the phz1 cluster, phzM and phzS (Rampioni et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the LasR quorum-sensing system of P. aeruginosa is regulated by prequorum and post-quorum regulating systems 86 . The first system is controlled by post-translational repressors QscR, QslA and QteE 20, [86][87][88][89] . In the absence of 3OC12-HSL, they can each form a heterodimer with LasR.…”
Section: Discussionmentioning
confidence: 99%
“…All these interactions indirectly change the conformation of the DBD, thus allosterically preventing DNA binding. It was previously shown that QslA can bind to LasR and thereby inhibit its DNA-binding capability 86 . Moreover, it has been shown that QslA supresses formation of the LasR homodimer complex by occupying the same surface area that is used for dimerization 88,89 .…”
Section: Discussionmentioning
confidence: 99%